The second life of snap - Kelly, Erin Entrada (Greenwillow Books, an Imprint of HarperCollins Publishers, 2026)
Twelve-year-old Zuzu befriends a guardian robot with a limited battery life that was given to her father as severance after being laid off from the mega corporation that controls everything.